47th AIAA/ASME/SAE/ASEE Joint Propulsion Conference &Amp;amp; Exhibit 2011
DOI: 10.2514/6.2011-6143
|View full text |Cite
|
Sign up to set email alerts
|

Focused Solar Ablation: A Nanosat-Based Method for Active Removal of Space Debris

Abstract: A novel concept for the active removal of space debris using solar power is proposed. Focused solar ablation is an in-space propulsion concept based on using concentrator mirrors on nanosats and using the solar power to evaporate material from the debris to produce deceleration thrust thereby providing the ∆V necessary to deorbit. An energy balance is used along with free-molecular effusion theory to estimate the thrust produced by the concept and the corresponding deorbit times for an aluminum debris masses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…This device could also be used as a main drive for nanospace-craft of Figure 1. Nanosat based removal of space debris using focused solar ablation [2] . The proposed electric/chemical micropropulsion system is enabling nanosat maneuvering and precise station keeping.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This device could also be used as a main drive for nanospace-craft of Figure 1. Nanosat based removal of space debris using focused solar ablation [2] . The proposed electric/chemical micropropulsion system is enabling nanosat maneuvering and precise station keeping.…”
Section: Introductionmentioning
confidence: 99%
“…The nanosatellite uses a dual-mode microthruster to reduce orbit lifetime of space junk by the reactive force generated by solar ablation. [2] Preliminary studies [3] using the direct simulation Monte Carlo method have shown that plugannular chemical (PAC) micronozzle offers higher thrust than conventional designs due to a better utilization of pressure thrust. Isp has been increased by more than 100% over convergingdiverging nozzles at low Reynolds numbers.…”
Section: Introductionmentioning
confidence: 99%